The contribution of diaspora remittances to household food security in the Tsholotsho District, Zimbabwe - Marambanyika, Thomas; Ndlovu, Clara (Nova Science Publishers, 2019)
Zimbabwe has been experiencing economic crisis since the turn of the 21st century, resulting in most economical active people mainly in the southern districts, including Tsholotsho, migrating to surrounding countries in the SADC region, especially South Africa. Despise the prevailing semi-arid conditions affecting predominantly rain-fed agriculture being worsened by the apparent effects of climate change, human movements further disrupted food security strategies which local communities were accustomed to. Therefore, this paper assessed the contribution of diaspora remittances to household food security in Ward 9 Chefunye, Tsholotsho district in Zimbabwe. Data were collected through a questionnaire targeting a total of one hundred and twenty-four households receiving and not receiving remittances and key informant interviews with development partners, government departments and local leadership. A comparison ...